Optical absorption in annealed tin sulphide thin films - Sakrani, Samsudi; Deraman, Karim; D. Hutagalung, Sabar; Wahab, Yusof; Ismail , Bakar (Malaysian Solod State Science and Technology Society, 1994)

(untitled)
Evaporated thin sulphide thin films have been prepared onto glass substrate at room temperature. The films were subjected to long period annealing in running argon gas up to 36 hours. Optical absorption measurements were made on the as prepared and annealed films near the fundamental absorption edge over the visible light vision light regions. Absorption coefficient, ï¡ were found to be of the order 10-5 cm-1 which suggest the occurance of indirect optical transition. A further investigation on the (ï¡hï®)1/2 and (ï¡hï®)1/3 plots revealed the existence of indirect allowed and indirect forbidden transition near the absorbtion edge respectively. The resulting optical band gap of the former were found to be 1.33 eV (as prepared) and between 1.59- 2.01 eV (annealed films) and this values were associated with compositional changes during annealing; the mainly SnS stoichiometric composition of the as prepared films was gradually disproportionated to SnS2 and completion of the course took place at the end 20 hours annealing. The optical band gap of 2.01 eV was in good agreement with those measured earlier on SnS2 in both thin film and bulk forms.